2018
DOI: 10.21303/2504-5695.2018.00682
|View full text |Cite
|
Sign up to set email alerts
|

The Study of the Possibility of Combining Freshwater Fish With Duck Meat in Meat-Containing Semi-Finished Products

Abstract: It is an urgent direction of studies to ground a possibility of combining different types of raw materials at producing semi-products. It is prospective in creating new types of products to combine white silver carp and silver crucian and regional duck in recipes of meat-containing semi-products for raising their functional and technological indices and biological effectiveness at preserving quality organoleptic characteristics in the traditional technology of meat-containing cut semi-products. There were ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Variants of formulations are given in Table 1. Materials and methods applied in the research into a set of indicators for the developed meat-containing semi-finished products are described in detail in paper [23].…”
Section: Materials and Methods To Study A Set Of Indicators For The Dmentioning
confidence: 99%
“…Variants of formulations are given in Table 1. Materials and methods applied in the research into a set of indicators for the developed meat-containing semi-finished products are described in detail in paper [23].…”
Section: Materials and Methods To Study A Set Of Indicators For The Dmentioning
confidence: 99%
“…The use of a composition of rosemary and grape seed extracts also reduces the rate of lipid oxidation. The study (Bozhko & Pasichnyi, 2018) investigated the effectiveness of introducing such a composition into minced meat from Peking duck. It was found that the addition of rosemary extract (0.01-0.03%) and grape seeds (0.05-0.15%) helps slow down the hydrolytic lipid oxidation of minced meat by 35.63-57.09%.…”
Section: Armenteros Et Al (2013) and Ganhão Et Al (2013)mentioning
confidence: 99%